1984
DOI: 10.1677/joe.0.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to a progestin via milk alters subsequent LH cyclicity in the female rat

Abstract: Medroxyprogesterone acetate (MPA; 5 micrograms/g body wt) or norethisterone oenanthate (NET-OEN; 4 micrograms/g body wt) was given to lactating female rats by subcutaneous injection 1 day after parturition. Each female suckled ten female pups which had been randomly allocated to her and at 21 days of age the pups were weaned. In this way female pups were exposed to either MPA or NET-OEN via milk during suckling. The patterns of LH and progesterone secretion at pro-oestrus were investigated using radioimmunoass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…From studies using tracer compounds conducted in our laboratory, we have shown that MPA is not significantly metabolized by the maternal physiology before being transferred to milk, although it does appear to be metabolized by the time that it has passed into the pups' plasma (Holzhausen, 1982). There is a possibility that androgenic metabolites are produced, since we have observed some apparently androgenic (i.e., masculinizing) effects of neonatal MPA exposure in rats (Birke, Holzhausen, Murphy, & Sadler, 1984;Holzhausen et al, 1984). Whether or not this might be the mechanism by which maternal licking rates are altered by MPA is not clear at present.…”
Section: Discussionmentioning
confidence: 86%
“…From studies using tracer compounds conducted in our laboratory, we have shown that MPA is not significantly metabolized by the maternal physiology before being transferred to milk, although it does appear to be metabolized by the time that it has passed into the pups' plasma (Holzhausen, 1982). There is a possibility that androgenic metabolites are produced, since we have observed some apparently androgenic (i.e., masculinizing) effects of neonatal MPA exposure in rats (Birke, Holzhausen, Murphy, & Sadler, 1984;Holzhausen et al, 1984). Whether or not this might be the mechanism by which maternal licking rates are altered by MPA is not clear at present.…”
Section: Discussionmentioning
confidence: 86%
“…Chronic progesterone exposure during the first 3 weeks of life can induce ovulatory failure in rats (Bukovsky, Presi & Krabec, 1979). Similarly, neonatal exposure to MPA has been shown to depress the amplitude of the LH surge (Holzhausen, 1982;Holzhausen et al, 1984), and in an apparently dose-dependent fashion. The slight reduction in adrenal weight after exposure to MPA via the milk in neonatal life seems to be even more pronounced when MPA or progesterone are injected directly (Logothetopoulos et al, 1961 ;Tapanainen, 1979).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that steroids do pass into the lipid fraction of milk ; their subsequent effects will then depend, in part, upon the extent to which they are orally active. Oestrogens(Hain, 1935) and progestagens(Hull, 1981;Holzhausen, 1982;Holzhausen, Murphy &Birke, 1984) have been shown to affect sexual differentiation in rats after ingestion in milk.© 1984 Journals of Reproduction & Fertility LtdDownloaded from Bioscientifica.com at 08/29/2020 07:38:13PM via free access…”
mentioning
confidence: 99%
“…When rats are given oral doses of methyl‐acetoxyprogesterone, a synthetic progestin, from days 15 to 20 of gestation, female pups display clitoral hypertrophy, increased anogenital distance, urethrovaginal fistulas, and blind vaginas [56]. Holzhausen et al [57] reported that maternal administration of another progestin, medroxyprogesterone acetate (postnatal day 1 at 5 μg/g sc), defeminizes the female pups such that they fail to display a proestrus LH surge after puberty. Neonatal treatment with the progesterone antagonist mifepristone (1 mg sc every other day for the first 15 d of life) causes structural abnormalities of the oviducts, infertility, PVC, anovulatory polyfollicular ovaries, and elevated serum levels of follicle‐stimulating hormone [58].…”
Section: Mammalian Sexual Differentiationmentioning
confidence: 99%